Targeting the Erythrocytic and Liver Stages of Malaria Parasites with s‐Triazine‐Based Hybrids. Issue 5 (17th March 2015) - Rodrigues, Catarina A. B.; Frade, Raquel F. M.; Albuquerque, Inês S.; Perry, Maria J.; Gut, Jiri; Machado, Marta; Rosenthal, Philip J.; Prudêncio, Miguel; Afonso, Carlos A. M.; Moreira, Rui
Abstract A diversity‐oriented library of s‐triazine‐based hybrids was screened for activity against the chloroquine‐resistant Plasmodium falciparum W2 strain. The most striking result was sub‐micromolar activity against cultured erythrocytic‐stage parasites of hybrid molecules containing one or two 8‐aminoquinoline moieties. These compounds were not clearly toxic to human cells. The most effective blood‐schizontocidal s‐triazine derivatives were then screened for activity against the liver stage of malaria parasites. The s‐triazine hybrid containing two 8‐aminoquinoline moieties and one chlorine atom emerged as the most potent against P. berghei liver‐stage infection, active in the low nanomolar region, combined with good metabolic stability in rat liver microsomes. These results indicate that s‐triazine‐8‐aminoquinoline‐based hybrids are excellent starting points for lead optimization as dual‐stage antimalarials.